2002
DOI: 10.1177/030089160208800614
|View full text |Cite
|
Sign up to set email alerts
|

Are International Guidelines for the Prescription of Adjuvant Treatment for Early Breast Cancer Followed in Clinical Practice? Results of a Population-Based Study on 1547 Patients

Abstract: Despite the availability of official and authoritative guidelines, adjuvant treatment prescription for early breast cancer in Lombardy in 1997 was suboptimal, especially in well-defined subgroups of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…These problems could lead to overtreatment or undertreatment in Ki-67 Expression in Early Breast Cancerclinical practice. 3,39,40 One problem is that the number of patients in the low-risk group is too small. In this study, only 196 patients (18.4%) were classified in the low-risk group.…”
Section: Discussionmentioning
confidence: 99%
“…These problems could lead to overtreatment or undertreatment in Ki-67 Expression in Early Breast Cancerclinical practice. 3,39,40 One problem is that the number of patients in the low-risk group is too small. In this study, only 196 patients (18.4%) were classified in the low-risk group.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that higher intermediate test scores [25][26][27][28][29][30] are more likely to yield a CT recommendation, demonstrating that all patients within the intermediate RS category are not considered by physicians to have the same risk for recurrence [20]. Until the results of the TAILORx trial emerge [41] (to assess CT benefit in patients with RS [11][12][13][14][15][16][17][18][19][20][21][22][23][24]), Irish oncologists will continue to balance additional clinico-pathological factors in making adjuvant treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…There is a wide variation in adjuvant CT recommendations among medical oncologists, unexplained by clinicopathological factors such as age, tumour size and histology alone [3,[9][10][11][12][13][14]. The use of novel prognostic and predictive tools in evaluating prognosis and informing treatment decisions can aid the appropriate selection of patients for CT, and may therefore reduce the cumulative clinical burden and cost of breast cancer management [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…However, all these factors were known at the department of this study and were taken into account. Therefore we had expected a much higher adherence rate [11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%